2018
DOI: 10.3847/1538-4357/aae688
|View full text |Cite
|
Sign up to set email alerts
|

Oscillator Strengths for Ultraviolet Transitions in P ii: The Multiplet at 1308 Å

Abstract: We report lifetimes, branching fractions, and the resulting oscillator strengths for transitions within the P II multiplet (3s 2 3p 2 3 P − 3s3p 3 3 P o ) at 1308 Å. These comprehensive beam-foil measurements, which are the most precise set currently available experimentally, resolve discrepancies involving earlier experimental and theoretical results. Interstellar phosphorus abundances derived from λ1308 can now be interpreted with greater confidence. In the course of our measurements, we also obtained an exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…Schectman et al (2005) found contaminating lines from highly-ionized chlorine (Cl IV and V) in their THIA data on Cl II, too. The same situation was observed by Brown et al (2018) in their work on P II. Further measurements at 170 keV were produced on the Cl V line at 545.11 Å to establish its short lifetime.…”
Section: Methodssupporting
confidence: 83%
“…Schectman et al (2005) found contaminating lines from highly-ionized chlorine (Cl IV and V) in their THIA data on Cl II, too. The same situation was observed by Brown et al (2018) in their work on P II. Further measurements at 170 keV were produced on the Cl V line at 545.11 Å to establish its short lifetime.…”
Section: Methodssupporting
confidence: 83%
“…Jenkins (2009) adopted theoretical P ii f -values originally obtained by Hibbert (1988). However, more precise experimentallydetermined f -values for the important λ1152 and λ1301 transitions are now available (Federman et al 2007;Brown et al 2018). These new experimental results indicate that the P ii column densities obtained from the λ1152 and λ1301 transitions should be revised downward by 0.045 dex and 0.188 dex, respectively, in agreement with recent theoretical calculations (Tayal 2003;Froese Fischer et al 2006).…”
Section: Introductionsupporting
confidence: 68%
“…For our analysis of P ii column densities, we adopt the experimentally determined oscillator strength for the P ii λ1301 transition recently published by Brown et al (2018). Their f -value for P ii λ1301 indicates that a downward revision of 0.188 dex should be applied to column densities derived using the older Hibbert (1988) fvalue (which is the one recommended by Morton 2003).…”
Section: Phosphorus Column Densitiesmentioning
confidence: 99%
“…For absorp-tion lines of interest we constructed theoretical Voigt line profiles from initial estimates of v, N, and b, and allowed these parameters to vary until a minimum in χ 2 between profile and data was reached. Oscillator strengths for the lines were taken from Morton (2003), Kisielius et al (2014) (S II), Federman et al (2007) (P II λ1152), or Brown et al (2018) (P II λ1301). Theoretical line profiles were convolved with COS Line Spread Functions (LSFs) constructed by interpolating LSF tables 2 to the relevant wavelength.…”
Section: Line Identification and Profile Fittingmentioning
confidence: 99%